2020
DOI: 10.1155/2020/7458239
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Computer‐Aided Process Planning for Hybrid Additive/Subtractive Process

Abstract: The hybrid process, which integrates two or more different processes such as additive manufacturing and subtractive manufacturing, has gained appreciable considerations in recent years. This process exploits the benefits of individual processes while overcoming their limitations. Lately, the combination of additive, subtractive, and inspection methods is a valuable conglomeration, considering its potential to produce complicated components precisely. Certainly, computer-aided process plan (CAPP) provides a cru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Abdulhameed et al. (2020) considered that a CAPP deals with the following actions: (i)feature recognition from the geometrical model; (ii)selection of machine tools; (iii)selection of tool sets; (iv)selection of machine setup; (v)selection of machining operations and their sequence; (vi)selection of cutting tools; (vii)calculation of cutting conditions; (viii)determination of tool paths; and (ix)numerical control (NC) part program generation. …”
Section: Process Planning and Schedulingmentioning
confidence: 99%
See 1 more Smart Citation
“…Abdulhameed et al. (2020) considered that a CAPP deals with the following actions: (i)feature recognition from the geometrical model; (ii)selection of machine tools; (iii)selection of tool sets; (iv)selection of machine setup; (v)selection of machining operations and their sequence; (vi)selection of cutting tools; (vii)calculation of cutting conditions; (viii)determination of tool paths; and (ix)numerical control (NC) part program generation. …”
Section: Process Planning and Schedulingmentioning
confidence: 99%
“…Figure 8 shows the schematic representation of a basic CAPP model and the contact point with the scheduling, represented by the block in red. Abdulhameed et al (2020) considered that a CAPP deals with the following actions: (Marri et al, 1998). Tan and Khoshnevis (2000) indicated that there are four decision-making approaches frequently used in the implementation of a CAPP system: (i) decision logic: determines how a process (or processes) is selected.…”
Section: Computer-aided Process Planningmentioning
confidence: 99%